Possible risk factors for postoperative urinary tract infection following ureteroscopic lithotripsy - Jovanović Mirko; Bančević Vladimir; Košević Branko; Aleksić Predrag; Šuljagić Vesna (Vojnosanitetski Pregled)
Background/Aim. Ureteroscopic lithotripsy is today a safe method of endoscopic destruction of stone in the kidney and ureter with a small number of complications of which the most common is postoperative urinary tract infection. Risk factors for the occurrence of urinary tract infection after the ureteroscopic destruction of stones in the ureter and kidney are not clearly defined in the previous studies. Methods. The study included 389 patients with ureteroscopic lithotripsy and possible risk factors were analyzed: age of the patients, sex, diabetes presence, degree of hydronephrosis, stone size, stone localization, wear of ureteral JJ stent and percutaneous nephrostomy catheter, type of surgical procedure and duration of the operation. The frequency of postoperative urinary tract infection was statistically analyzed in relation to the possible risk factors. Results. Ten percent of the patients had postoperative urinary tract infection. The higher incidence of postoperative urinary tract infection was found in patients with diabetes (χ2 = 22.918; p < 0.001), those who before surgery carried a ureteral JJ stent (χ2 = 4.620; p = 0.040) and percutaneous nephrostomy catheter (χ2 = 8.240; p = 0.004), who had a larger stone (χ2 = -3.301; p = 0.001), and whose surgery lasted longer (t = 4.261; p < 0.001). Conclusion. The frequency of postoperative urinary infection and risk factors for its emergence in our study are in line with the results of studies by other authors. Patients with diabetes, who preoperatively carried JJ stent or a percutaneous nephrostomy catheter, who had large stones and in which the operating time is longer have a greater risk of developing postoperative urinary tract infection. Accordingly, the importance of identifying these patients in the preparation for ureteroscopic lithotripsy contributes to the appropriate preoperative preparation and decreases the frequency of postoperative urinary tract infection to a minimum.